Immigrants and Legal Status: Do Personal Contacts Matter? - Simone Cremaschi; Carlo Devillanova (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
This paper addresses the effect of personal contacts on immigrants' legal status by focusing particularly on the contacts' direct links to legal status and indirect associations with the labor market. The overall effect of these contacts is theoretically unsigned and likely to vary across contact type and contextual factors. Our empirical analysis, based on unique Italian survey data on both documented and undocumented immigrants, tests two hypotheses regarding native contacts: (i) that they are more likely to be associated with a higher immigrant documentation probability and (ii) that they are more likely to introduce immigrants to jobs that facilitate access to employment-based legalization initiatives. Our results indicate that contacts with both natives and family members have a direct, positive, and quantitatively large effect on immigrant documentation probability, whereas contacts with members of the same ethnic group only indirectly increase documentation probability by raising the probability of employment. Our findings also support the hypothesis that native contacts connect immigrants with better jobs.
Keywords: 330; Immigrant integration; legal status; personal contacts; networks; labor market outcomes